Constraining paleo PGA values by numerical analysis of overturned columns. - Yagoda-Biran, Gony
The estimated peak ground acceleration (PGA) for a specific region cannot always be determined reliably from compilation and statistical analyses of instrumental data acquired because of the relatively short time window available for such an approach, typically up to 100 years of instrumentation. We propose a complimentary approach for estimating PGA in a specific region, through back analysis of seismically driven column collapse in historic monuments, using the numerical discrete element discontinuous deformation analysis (DDA) method. Preliminary threshold 'paleo PGA' values thus obtained constrain the lower bound of PGA estimates using information from a much broader time window, in the case study presented here of approximately 1200 years.
Keywords: Numerical analysis; Discrete element methods; DDA; PGA; Paleo-seismicity.; Historical monuments